2003
DOI: 10.1002/jsfa.1546
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of fluoride by tea plant (Camellia sinensis L) and the impact of aluminium

Abstract: Tea plant (Camellia sinensis L) accumulates large amounts of fluoride in mature leaves from soils of normal fluoride availabilities, but the properties of fluoride absorption by this plant species are not well understood. The present study examined the characteristic of fluoride uptake by tea plants and the impact of Al with solution and soil experiments. The results showed that the fluoride taken up by tea plants was largely and readily transported, in particular to the leaves. The fluoride in leaves increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 12 publications
3
50
1
3
Order By: Relevance
“…A comparison of the values in Table 2 also indicates that the other species appeared to accumulated lower amounts of F -somewhat, especially the waterweed E. nuttallii L. Besides, species appeared to accumulated lower amounts of F -in lower F --concentration culture. Similar findings are reported by Ruan, who summarized that F --uptake by Camelia sinensis L. tea plants was linearly correlated to external F --concentration (Ruan et al 2003).…”
Section: Resultssupporting
confidence: 78%
“…A comparison of the values in Table 2 also indicates that the other species appeared to accumulated lower amounts of F -somewhat, especially the waterweed E. nuttallii L. Besides, species appeared to accumulated lower amounts of F -in lower F --concentration culture. Similar findings are reported by Ruan, who summarized that F --uptake by Camelia sinensis L. tea plants was linearly correlated to external F --concentration (Ruan et al 2003).…”
Section: Resultssupporting
confidence: 78%
“…Nagata et al (1993) studied the forms of F and Al in tea plant and indicated the evidence of Al-F complexes in tea tissues. Ruan et al (2003) examined the characteristic of fluoride uptake by tea plants and the impact of Al. Xie et al (2001) reported the relationships between Al and F in soil profiles of an abandoned tea plantation in Hong Kong and their uptake by six woody species, but they did not investigate the relationship between Al and F concentrations in soil, and Al and F contents in tea plant.…”
Section: Introductionmentioning
confidence: 99%
“…The fluoride content in various tea sorts has been reported e.g. by Cao et al (2004), Jin et al (2006), Mahvi et al (2006), some authors also discussed the impact of aluminium (Ruan et al 2003;Street et al 2007).…”
mentioning
confidence: 93%